2013
DOI: 10.1523/jneurosci.0410-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Neural Network Reorganization Associated with Second Language Vocabulary Acquisition: A Multimodal Imaging Study

Abstract: It remains unsettled whether human language relies exclusively on innately privileged brain structure in the left hemisphere or is more flexibly shaped through experiences, which induce neuroplastic changes in potentially relevant neural circuits. Here we show that learning of second language (L2) vocabulary and its cessation can induce bidirectional changes in the mirror-reverse of the traditional language areas. A cross-sectional study identified that gray matter volume in the inferior frontal gyrus pars ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
140
6
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(175 citation statements)
references
References 80 publications
22
140
6
7
Order By: Relevance
“…However, these last two studies used a completely different measure and methodology to those of the former studies. In line with results in cross-sectional studies, there are also two longitudinal studies: one showed increased FA in CC for learners vs. non-learners (Schlegel et al, 2012) and another one showed increased WM volume inside the right IFG (Hosoda et al, 2013).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…However, these last two studies used a completely different measure and methodology to those of the former studies. In line with results in cross-sectional studies, there are also two longitudinal studies: one showed increased FA in CC for learners vs. non-learners (Schlegel et al, 2012) and another one showed increased WM volume inside the right IFG (Hosoda et al, 2013).…”
Section: Resultssupporting
confidence: 82%
“…Hypothesis (Abutalebi & Green, 2007;Green & Abutalebi, 2013), there is just one region predicted by the model that consistently shows up across studies as a structural difference due to bilingualism: the left/right IFG (Hosoda et al, 2013;Klein et al, 2014;Grogan et al, 2012;Luk et al, 2011;García-Pentón et al, 2014). Some of the studies used alternatives to the traditional methods of VBM and ROI-based analysis and analyzed the whole brain to reveal effects of bilingualism in the IFG and in the connections between there and other regions (Luk et al, 2011;Klein et al, 2014;García-Pentón et al, 2014).…”
Section: Assessing These Findings In the Light Of Abutalebi And Greenmentioning
confidence: 98%
See 1 more Smart Citation
“…Further evidence for the effects of late L2 learning was presented by Hosoda and colleagues (23), who reported a crosssectional and a longitudinal study on Japanese learners of English. Participants in the cross-sectional study demonstrated a positive correlation between the size of their L2 vocabulary and the FA values in the right hemisphere, including the subcortical WM beneath IFG, the arcuate fasciculus, and the IFGcaudate nucleus and IFG-superior temporal gyrus pathways.…”
mentioning
confidence: 88%
“…Although it appears that WM changes are to be expected in early bilinguals, the evidence on late bilinguals is still inconclusive. There is evidence that linguistic training can indeed affect WM structure (22), but it also appears that these effects might be temporary if the training is terminated (23). In this study, we scanned a group of highly proficient and highly immersed late L2 speakers of English who did not receive any linguistic training at the time of testing and compared them with a group of monolinguals with a TBSS analysis.…”
mentioning
confidence: 99%